Lynx lynx subsp. lynx Linnaeus 1758 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Lynx lynx subsp. lynx Linnaeus 1758 Lynx lynx subsp. lynx Linnaeus 1758, Syst. Nat., 10th ed., Vol. 1: 43. Type Locality: "Europe sylvis and desertis", subsequently restricted by Thomas (1911 a :136) to "Wennersborg, S. Sweden ". Synonyms: Lynx lynx subsp. albus Kerr 1792; Lynx lynx subsp. baicalensis (Dybowsky 1922); Lynx lynx subsp. borealis (Thunberg 1798); Lynx lynx subsp. carpathica (Heptner 1972); Lynx lynx subsp. cervarius Temminck 1824; Lynx lynx subsp. dinniki Satunin 1915; Lynx lynx subsp. guttatus Smirnov 1922; Lynx lynx subsp. kattlo (Schrank 1798); Lynx lynx subsp. lupulinus (Thunberg 1825); Lynx lynx subsp. lynculus (Nilsson 1820); Lynx lynx subsp. melinus Kerr 1792; Lynx lynx subsp. neglectus Stroganov 1962; Lynx lynx subsp. orientalis Satunin 1905; Lynx lynx subsp. virgata (Nilsson 1829); Lynx lynx subsp. vulgaris Kerr 1792; Lynx lynx subsp. vulpinus (Thunberg 1825); Lynx lynx subsp. wrangeli Ognev 1928. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Carnivora, pp. 532-628 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 541, DOI: 10.5281/zenodo.7316519